Food is the basic need of every people that has to be fulfilled in order to create stable food security. The different population growth can differ the food requirement that has to be fulfilled by self production. Thus, this also differ food agricultural land size requirement. The general objective of this research was to analyze food agricultural land size requirement in fulfilling food requirement of population in West Lampung District. This research was conducted by using retrospective de - Sumarlin .; Yayuk F. Baliwati; Ernan Rustiadi; Wafda . (Forum Pasca Sarjana, 2009)
Food is the basic need of every people that has to be fulfilled in order to create stable food security. The different population growth can differ the food requirement that has to be fulfilled by self production. Thus, this also differ food agricultural land size requirement. The general objective of this research was to analyze food agricultural land size requirement in fulfilling food requirement of population in West Lampung District. This research was conducted by using retrospective design and secondary data which then analyzed descriptively. The research used some data, they were: (1) demography data year 2001-2007 from Central Bureau of Statistics, (2) food balance sheet data year 2007 from Food Security Board of West Lampung District, (3) food consumption data year 2007 from Agriculture and Food Security Office of Lampung Province, (4) production data, productivity data, and plant index year 2002-2007 from Crops and Horticulture Office of West Lampung District, and 5) land potential of food agricultural development year 2004 from National Survey and Mapping Coordination Board. The result of the research indicates that rice requirement in West Lampung District until year 2012 can be fulfilled by production with land size utilized for rice planting in 2007. In other hand, to reach ideal cassava production, it needs 489 hectare land size increasing with land productivity 20,22 ton/ha, per capita consumption 41,33 kg/year and population growth 1,683% per year. Keywords: food requirement, agricultural land size requirement, staple food